The paradigm shift in third world theologies of liberation : from socio-economic analysis to cultural analysis. Assesment and status of the question - De Schrijver, Georges (Leuven : Bibliotheek van de Faculteit Godgeleerdheid, 1996)
BMLIK
Engels
Brochure
Keywords: derde wereld